Oxidation of Manus Basin back-arc basalts increases with the addition of melts from altered oceanic crust - Janine L. Andrys; Katherine A. Kelley; Elizabeth Cottrell (Earth and Planetary Science Letters, 2026)

Late Miocene garnet-bearing andesites in the Northern Andes and their tectonic implications - Susana Hoyos; Marion Weber; Andrés L. Cárdenas-Rozo; José F. Duque Trujillo; Elizabeth Cottrell; Alejandro Beltrán-Triviño; Albrecht von Quadt; Jorge Gómez Tapias (International Geology Review, 2026)

Citation for the 2025 Clarke Award to Suzanne K. Birner - Elizabeth Cottrell (Geochimica et Cosmochimica Acta, 2025)

The effect of pressure on sulfur valence state in mafic silicate melts - Michelle J. Muth; Elizabeth Cottrell (Earth and Planetary Science Letters, 2025)

The Volcanoes of the World database - Benjamin J. Andrews; Edward Venzke; Elizabeth Cottrell; Sally S. K. Sennert; Kadie L. Bennis; A. E. J. Crafford (Bulletin of Volcanology, 2025)

Fe Kα XANES, Fe Kβ HERFD XANES and EPMA flank method determinations of the oxidation state of Fe in garnet - Megan Holycross; Elizabeth Cottrell; Jay Ague; Antonio Lanzirotti; Matthew Newville (Chemical Geology, 2024)

Retraction notice to “Experimental determination of ferric iron partitioning between pyroxene and melt at 100 kPa” [CHEMGE 584 (2021) 120532] - Avishek Rudra; Elizabeth Cottrell; Marc M. Hirschmann (Chemical Geology, 2023)

Nitrogen partitioning between silicate phases and aqueous fluid depends on concentration - Colin R.M. Jackson; Elizabeth Cottrell (Geochimica et Cosmochimica Acta, 2023)

No detectable redox exchange between sulfur and iron during rapid cooling of basalts - Michelle J. Muth; Elizabeth Cottrell (Earth and Planetary Science Letters, 2023)

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

Correction to: Partitioning of Fe2O3 in peridotite partial melting experiments over a range of oxygen fugacities elucidates ferric iron systematics in mid-ocean ridge basalts and ferric iron content of the upper mantle - Fred A. Davis; Elizabeth Cottrell (Contributions to Mineralogy and Petrology, 2022)

Direct nanoscale observations of degassing-induced crystallisation in felsic magmas - Mattia Pistone; Eric Formo; Alan G. Whittington; Thomas Herbst; Elizabeth Cottrell (Contributions to Mineralogy and Petrology, 2022)

Experimental quantification of vanadium partitioning between eclogitic minerals (garnet, clinopyroxene, rutile) and silicate melt as a function of temperature and oxygen fugacity - Megan Holycross; Elizabeth Cottrell (Contributions to Mineralogy and Petrology, 2022)

Partitioning of Fe2O3 in peridotite partial melting experiments over a range of oxygen fugacities elucidates ferric iron systematics in mid-ocean ridge basalts and ferric iron content of the upper mantle - Fred A. Davis; Elizabeth Cottrell (Contributions to Mineralogy and Petrology, 2021)
Basalts and peridotites from mid-ocean ridges record f O2 near the quartz-fayalite-magnetite buffer (QFM), but peridotite partial melting experiments have mostly been performed in graphite capsules (~ QFM-3), precluding evaluation of ferric iron’s behavior during basalt generation. We performed experiments at 1.5 GPa, 1350–1400 °C, and f O2 from about QFM-3 to QFM+3 to investigate the anhydrous partitioning behavior of Fe 2 O 3 between silicate melts and coexisting peridotite mineral phases. We find spinel/melt partitioning of Fe 2 O 3 ( $${D}_{\mathrm{Fe}2\mathrm{O}3}^{\mathrm{spl}/\mathrm{melt}}$$ D Fe 2 O 3 spl / melt ) increases as spinel Fe 2 O 3 concentrations increase, independent of increases in f O2 , and decreases with temperature, which is consistent with new and previous experiments at 0.1 MPa. We find $${D}_{\mathrm{Fe}2\mathrm{O}3}^{\mathrm{opx}/\mathrm{melt}}$$ D Fe 2 O 3 opx / melt = 0.63 ± 0.10 and $${D}_{\mathrm{Fe}2\mathrm{O}3}^{\mathrm{cpx}/\mathrm{melt}}$$ D Fe 2 O 3 cpx / melt = 0.78 ± 0.30. MORB Fe 2 O 3 and Na 2 O concentrations are consistent with a modeled MORB source with Fe 2 O 3 = 0.48 ± 0.03 wt% (Fe 3+ /ΣFe = 0.053 ± 0.003) at potential temperatures ( T P ) from 1320 to 1440 °C. The temperature-dependence of the $${D}_{\mathrm{Fe}2\mathrm{O}3}^{\mathrm{spl}/\mathrm{melt}}$$ D Fe 2 O 3 spl / melt function alone allows ~ 40% of the variation in MORB compositions. If we allow $${D}_{\mathrm{Fe}2\mathrm{O}3}^{\mathrm{opx}/\mathrm{melt}}$$ D Fe 2 O 3 opx / melt and $${D}_{\mathrm{Fe}2\mathrm{O}3}^{\mathrm{opx}/\mathrm{melt}}$$ D Fe 2 O 3 opx / melt to also vary with temperature by tying them to spinel Fe 2 O 3 through intermineral partitioning, then all the MORB data are within error of the model. Our model Fe 2 O 3 concentration for the MORB source would require that the convecting mantle be more oxidized at a given depth than recorded by continental mantle xenoliths. Our result is supported by thermodynamic models of mantle with Fe 3+ /ΣFe = 0.03 that predict f O2 of ~ QFM-1 near the garnet-spinel transition, which is inconsistent with f O2 of MORB. Our results support previous suggestions that redox melting may occur between 200 and 250 km depth.

Considering land–sea interactions and trade‐offs for food and biodiversity - Richard S. Cottrell; Aysha Fleming; Elizabeth A. Fulton; Kirsty L. Nash; Reg A. Watson; Julia L. Blanchard (Global Change Biology, 2018)
With the human population expected to near 10 billion by 2050, and diets shifting towards greater per‐capita consumption of animal protein, meeting future food demands will place ever‐growing burdens on natural resources and those dependent on them. Solutions proposed to increase the sustainability of agriculture, aquaculture, and capture fisheries have typically approached development from single sector perspectives. Recent work highlights the importance of recognising links among food sectors, and the challenge cross‐sector dependencies create for sustainable food production. Yet without understanding the full suite of interactions between food systems on land and sea, development in one sector may result in unanticipated trade‐offs in another. We review the interactions between terrestrial and aquatic food systems. We show that most of the studied land–sea interactions fall into at least one of four categories: ecosystem connectivity, feed interdependencies, livelihood interactions, and climate feedback. Critically, these interactions modify nutrient flows, and the partitioning of natural resource use between land and sea, amid a backdrop of climate variability and change that reaches across all sectors. Addressing counter‐productive trade‐offs resulting from land‐sea links will require simultaneous improvements in food production and consumption efficiency, while creating more sustainable feed products for fish and livestock. Food security research and policy also needs to better integrate aquatic and terrestrial production to anticipate how cross‐sector interactions could transmit change across ecosystem and governance boundaries into the future.

Petrologic and experimental evidence for the movement and heating of the pre-eruptive Minoan rhyodacite (Santorini, Greece) - Elizabeth Cottrell; James E. Gardner; Malcolm J. Rutherford (Contributions to Mineralogy and Petrology, 1999)